Religiositas Matematika dalam Sekte Pythagorean - Kurniawan, Wiwit (Program Studi Studi Agama-Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2015)
Presently, mathematic is commonly known as scholarly studies specialized on worldly matters, step aside from mysticism. However, such perspective does not prevail on Pythagorean traditional sect. For this sect, mathematics constitutes divine activities and comprises of metaphysical elements. Pythagorean is a group of derived from Pythagoras disciples. Besides studying of mathematic, they also have tight tradition and mystical belief. This paper aims to analyze the religious side of Pythagorean sect which relates to mathematics. Many concept of mathematics in some universities recently come from Pythagoras thoughts. One of Pythagoras ideas used till now is Pythagoras’s theoretical framework of the comparative quadrate of trilateral sides, (a2+b2=c2). This mathematic concept is widely used, taught and taken as irrelevance with mystical matters, metaphysical and religiosity. The religious elements that have been analyzed refer to Durkheim’s concept of religion on belief in a sacred, namely totem, taboo and ritual. This study argues that Pythagorean conviction of mathematics, related to number, geometry and ratio are categorized as a kind of religious form. Pythagorean sect possessed belief to the sacred, totem, taboo and ritual which is connected with their conception on mathematics.